Sustainable tourism development – through case studies in Lao Cai province - Hau, Ha Thi; Ngoc, Ho Sy (Edelweiss Applied Science and Technology, 2026)
Based on the theory of sustainable tourism development, combining the analytical framework and evaluation criteria to approach three contents (development in terms of scale/quantity; quality of tourism services; and structure of tourism types and services). Based on the theoretical framework of the research thesis, the author conducted a random survey of 400 tourists in typical Lao Cai tourist areas (Sa Pa, Bac Ha, Bat Xat...) and concluded: (1) Although the total number of customers, products, and types of tourism are diverse, suitable, and increasing every year, there are still limitations that do not meet the needs of tourists at the peak of the tourist season, causing consequences for the brand, image, and environment at tourist destinations; (2) The quality and connection of services are assessed by tourists as not being as "expected" compared to the promotion and communication of typical tourism products and types of Lao Cai (from service quality, connection, and amenities), causing "negative" impacts on tourist destinations; (3) The structure of tourism products and types is not really diversified towards sustainable products to meet the needs of tourists.